Concomitant Third Molar Removal During Sagittal Split Osteotomy of the Mandible. Issue 1 (January 2016) - Sasaki, Ryo; Yao, Chuan-Fong; Chen, Ying-an; Lin, Cheng-Hui; Chen, Yu-Ray
Abstract : Abstract: It is described in textbook about management of third molar in orthognathic surgery that "ideally, the third molars should be removed 9 to 12 months before sagittal split osteotomy (SSO)." At the Chang Gung Craniofacial Center, the authors always remove mandibular third molars during SSO, because: removal of third molars at the same time of SSO could reduce psychological stress on patients by saving 1 surgical procedure under local anesthesia, better exposure of impacted third molars could be facilitated by sagittal split of buccal cortical plate, rigid fixation could be performed without difficulty by our fixation method using plates and screws crossover anterior oblique line. Strong force during the elevation of third molars, however, may result in the fracture of distal segment of SSO, where the buccal cortical plate is relatively thin because of the presence of third molar. Therefore, more care needs to be taken in the surgical technique, which is different from ordinary tooth extraction. In this paper, the details of surgical procedure of third molar removal during SSO were reported.